2020
DOI: 10.1099/mic.0.000923
|View full text |Cite
|
Sign up to set email alerts
|

The histone-like protein AlgP regulon is distinct in mucoid and nonmucoid Pseudomonas aeruginosa and does not include alginate biosynthesis genes

Abstract: The opportunistic bacterial pathogen Pseudomonas aeruginosa causes acute and chronic infections that are notoriously difficult to treat. In people with cystic fibrosis, <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Our discovery that AlgP affects polyP granule localization demonstrates that this protein remains important for starvation physiology. Although our AlgP mutant does not display a defect in cell cycle exit, there are intriguing clues that it may play a role in modulating gene expression and affect anaerobic survival(30). Indeed, AlgP was identified as highly expressed in the metabolically less active regions of P. aeruginosa biofilms using BONCAT labeling, suggesting that starvation upregulates its expression(31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our discovery that AlgP affects polyP granule localization demonstrates that this protein remains important for starvation physiology. Although our AlgP mutant does not display a defect in cell cycle exit, there are intriguing clues that it may play a role in modulating gene expression and affect anaerobic survival(30). Indeed, AlgP was identified as highly expressed in the metabolically less active regions of P. aeruginosa biofilms using BONCAT labeling, suggesting that starvation upregulates its expression(31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the sequence homology to PhaF, AlgP has interesting similarities in terms of sequence composition to the intrinsically disordered C-terminal tail of eukaryotic histone H1, also rich in lysine, proline, and alanine, as has been previously noted (12,27,30). Unlike the other core histones which are thought to have evolved from archaea, the histone H1 family is thought to be of bacterial origin (38).…”
Section: The C-terminus Of Algp: Connecting Polyp and Bacterial Chromatinmentioning
confidence: 89%
See 1 more Smart Citation
“…Prior studies have demonstrated that this C-terminal domain is a mutational hot spot in clinical isolates of P. aeruginosa from the lungs of cystic fibrosis (CF) patients, raising the possibility that algP may be under selective pressure in chronic infections ( 15 , 16 ). The C-terminal domain of AlgP has also previously been noted for its similarities to eukaryotic histone H1, due to its enrichment in lysine, alanine and proline residues, intrinsic disorder, and the ability of C-terminally-derived peptides to bind to DNA ( 14 , 15 , 17 , 18 ). We found that the C-terminus of AlgP is required for granule spacing but that AlgP does not play a role in efficient cell cycle exit during nitrogen starvation.…”
Section: Introductionmentioning
confidence: 90%
“…Finally, check out this month’s Editor’s Choice, selected by Senior Editor Gail Preston, concerning the function of the AlgP regulon in P. aeruginosa , from Ashley Cross ( @PresidentCross ) in the group of Joanna Goldberg at Emory University School of Medicine, USA with ex-Senior Editor Marvin Whiteley ( @whiteleylab ) [ 19 ]. And look out for our adverts for Editors, Senior Editors and our Deputy Editor in Chief – come and join us and help #publishingforthecommunity as we take the journal forward to its big celebration in 2022.…”
mentioning
confidence: 99%